2015
DOI: 10.3892/etm.2015.2851
|View full text |Cite
|
Sign up to set email alerts
|

Association of antibiotic resistance with SHV-12 extended-spectrum β-lactamase in Enterobacter cloacae

Abstract: Abstract.The association between antibiotic resistance and SHV-12 extended-spectrum β-lactamase (ESBL) in Enterobacter cloacae remains unknown. The aim of the present study was to investigate the prevalence of both chromosome-and plasmid-borne SHV-12 ESBL genes in Enterobacter cloacae. Transmission of the SHV-12 ESBL gene was explored, and the risk factors for antibiotic resistance in E. cloacae were analyzed. Polymerase chain reaction (PCR) results showed that 58 out of the 100 isolates carried the SHV-12 ESB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…cloacae was frequently implicated in nosocomial infections[ 1 , 2 ], and the production of pAmpC, ESBLs and carbapenemases have also led to the multidrug-resistance and high potential dissemination of clinical E . cloacae isolates[ 23 , 24 ]. Reports on MDR E .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…cloacae was frequently implicated in nosocomial infections[ 1 , 2 ], and the production of pAmpC, ESBLs and carbapenemases have also led to the multidrug-resistance and high potential dissemination of clinical E . cloacae isolates[ 23 , 24 ]. Reports on MDR E .…”
Section: Discussionmentioning
confidence: 99%
“…Unlike CTX-M-producers most frequent in Latin American countries[ 13 ], SHV was the dominant ESBL type with all identical to type 12 in this study ( Table 2 ). The proportion of SHV (75.0%) was higher than that in Guangdong China (58%) [ 23 ], and similar to that in Tunisia (77.8%) [ 24 ]. SHV-12, one of the most prevalent SHV types in Asia, can confer resistance against β-lactams, fluoroquinolones, aminoglycosides and sulfonamides, and its location and transmission efficiency were correlated closely with the antibiotic resistance of E .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ESBL which is ubiquitous and rampant among Enterobacteriaceae globally has been described by Liakopoulos et al (2016) as neglected yet ubiquitous. It is vital for resistance (Liu et al 2016). Liu et al (2016) showed that the location and transmission efficiency of SHV-12 ESBL are directly linked with the antibiotic resistance of Enterobacter cloacae.…”
Section: Shv Beta-lactamases (Class A)mentioning
confidence: 99%
“…It is vital for resistance (Liu et al 2016). Liu et al (2016) showed that the location and transmission efficiency of SHV-12 ESBL are directly linked with the antibiotic resistance of Enterobacter cloacae. Conjugation assays conducted by Liu et al (2016) which were transconjugated into E. coli C600 showed 84% partial expression and 10% complete expression of resistance from E. cloacae by plasmid-borne SHV-12 ESBL genes.…”
Section: Shv Beta-lactamases (Class A)mentioning
confidence: 99%